The Effect of Integrating an Educational Robot with Hypermedia on Students’ Acquisition of Scientific Concepts: The Case of Fifth-Grade Students - Ajlouni, Aseel O.; Jaradat, Suhair A. (International Journal of Interactive Mobile Technologies (iJIM), 2021)
This study was designed to reveal the effectiveness of integrating educational robots (ERs) with hypermedia in improving the acquisition of scientific concepts among fifth-grade students in Jordan. The present study utilized a pretest-posttest quasi-experimental design with a control group (CG) and an experimental group (EG). The participants of this study consisted of 50 fifth-grade female students attending a private school in the city of Amman during the 2019/2020 academic year. Participants’ ages ranged between (10-11) years old. The school was selected purposively, and classes were randomly assigned to the EG and the CG. In order to accomplish the aims of this study, a scientific concept test (SCT) was developed and its validity and reliability were ensured. The EG was taught a unit on motion and force by robot and hypermedia instruction, while the CG was taught the same unit by traditional instruction. Data was collected through administration of the presently developed SCT at pretest and posttest points. Then, this data was analyzed through covariance analysis. The findings of this analysis revealed that 66% of the variation in the fifth-grade students’ posttest SCT scores can be ascribed to the effect of teaching method. From this study, one can conclude that the integration of ERs with hypermedia has a positive impact on students’ acquisition of scientific concepts. These results may serve to encourage science teachers to integrate ERs with hypermedia when teaching scientific concepts.